FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL REMAJA DI CIREBON - Lisnawati Lisnawati; Nissa Sari Lestari (Care : Jurnal Ilmiah Ilmu Kesehatan, 2015)
Adolescent sexual behavior today tend permissive, many adolescents who engage in sexual activity ranging from mild to had sexual intercourse. Preliminary survey conducted on 24 students of SMK Negeri 1 Cirebon results are quite troubling to almost half of the respondents had severe sexual activity. The purpose of this study was to determine the factors associated with adolescent sexual behavior in SMK Negeri 1 Cirebon in 2013. The research was conducted using the method of analytic survey with cross sectional approach. Samples were students of class X SMK Negeri 1 Cirebon of 240 respondents drawn by systematic random sampling method. The research was conducted on May 2013 by using a primary data questionnaire. The results showed that the majority of students of SMK Negeri 1 Cirebon is male is 76.7%. Most students find information on reproductive health and sexual behavior of the media that is 60.8%. 64.2% students have enough knowledge about reproductive health and 72.1% students of mild sexual behavior. Based SPSS17 analysis using chi-square test showed that there is a relationship between gender and adolescent sexual behavior (P value 0.000), there was no correlation between the resources to adolescent sexual behavior (P value 0.093), there is a relationship between the level of adolescent knowledge about reproductive health with adolescent sexual behavior (P value 0.009)